If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = -3x + -7 Reorder the terms: 11 = -7 + -3x Solving 11 = -7 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 11 + 3x = -7 + -3x + 3x Combine like terms: -3x + 3x = 0 11 + 3x = -7 + 0 11 + 3x = -7 Add '-11' to each side of the equation. 11 + -11 + 3x = -7 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = -7 + -11 3x = -7 + -11 Combine like terms: -7 + -11 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| ln(x^2)+ln(16x)-2ln(2x)=3 | | 9+9x=54 | | 16-x=12+2x | | 4x/2+12=2 | | 12-7x=-65 | | -13+4x=-39+10x | | -7+6x=-37 | | x^2-54x-232=0 | | 5x-2+11+11=180 | | 3t^2+5t=-1 | | 5-4y=-20 | | 1=3(4)+b | | 61-2x=5-9x | | 4q+7=-13 | | 5=-1(3)+b | | 15*8=x | | 2x+13=-3-2x | | 3(3.5+m)=7.8 | | 21y=49 | | 9+8x=-19+x | | 5x^3+135-36=0 | | 4(6n-8)=68 | | 2(3x-5)+3=5(x-2)+5 | | 9=30x | | 56+=180 | | 10-4x=-2(3x-1) | | log(6)(x+33)-(log(6)(x-2))=2 | | 32n=8 | | 40+y=180 | | -5(x+2)-45=7-32 | | -7-3y=21 | | 6x-7+55=180 |